Effects of melatonin on blueberry fruit quality and cell wall metabolism during low temperature storage - QU,Guangfan (2022)
Abstract Melatonin is known to influence various physiological processes, including plant ripening; however, the effect of melatonin on postharvest blueberry fruit softening is unknown. Herein, the effects of melatonin at different concentrations (100, 300, and 500 μmol L-1) on the quality parameters, cell wall substances, cell-wall-degrading enzymes, and cell wall ultrastructure of blueberry fruits were investigated during low-temperature storage. Melatonin treatment was found to effectively delay the decline in fruit firmness, slow the loss of soluble solids and titratable acids, and decrease the respiration rate and decay rate of blueberry fruits. The blueberry fruits treated with 300 μmol L-1 melatonin exhibited the best quality. Melatonin treatment promoted anthocyanin accumulation, delayed ascorbic acid degradation, maintained a low relative membrane permeability in pulp, inhibited increases in lipoxygenase (LOX) activity, and reduced membrane lipid peroxidation. Moreover, melatonin controlled the formation of soluble pectin by inhibiting the activities of pectin methylesterase (PME), polygalacturonase (PG), cellulase (Cx), and β-glucosidase (β-Glu) while maintaining high contents of protopectin and cellulose. These results indicate that melatonin can effectively improve blueberry fruit quality and antioxidant capacity as well as and delay fruit softening by inhibiting the degradation of cell wall substances.